Within-person variability in performance across school subjects - Wright, Megan; von Stumm, Sophie (Learning and individual differences, 2022)
Although thought to be substantial, within-person variability in performance across school subjects has not been systematically studied. Here we analysed data from the Twins Early Development Study (TEDS; Nmax = 5919) to describe within-person variability across grades in English, maths, and science from age 7 to 16 years. We found that within-person grade variability was largely unstable across subjects and ages. Within-person grade variability at age 16 was not associated with any of 15 variables that typically explain between-person differences in school performance (e.g. IQ, socioeconomic status, and personality traits). Also, within-person grade variability did not predict later educational outcomes at ages 18 and 21. Within-person grade variability is observable, but did not emerge in this study as a meaningful psychological construct. We conclude that understanding the causes and consequences of within-person grade variability is possibly of limited epistemological value. •Students perform differently across school subject areas and years, giving rise to within-person grade variability.•Only 1% of individual differences in within-person grade variability were stable from age 7 through 16.•Within-person grade variability was not associated with factors that predict between-person differences in school grades.•Within-person grade variability did not emerge as a meaningful psychological construct.